Evaluation of the influence of elective postings in accordance with the competency-based undergraduate medical education pattern on the development of research abilities in students - Bhanupriya Shivshankar Pande; Shraddha Patel; Amit J Patil; Sonal R Deshpande; Aashutosh Ramakant Patel; Mohammed Usman Shaikh (Asian Journal of Medical Sciences, 2024)
Background: As per the revised competency-based medical education guidelines given by the National medical council of India, students are offered elective posting after the first part of 3rd phase of the medical professional course. This has been started from the year 2023. There will be various postings offered and at end of the posting they will be assessed on various domains. Aims and Objectives: Our study aims to assess the impact of elective posting on the research skills and students’ perception toward it. It also aims to identify the best methods to implement elective postings. Materials and Methods: In the year 2023, using a complete enumeration technique 86 students from the third phase of MBBS at a medical college in Maharashtra, India, were registered for the 2 months of elective and would be questioned twice following consent using a pre-validated questionnaire. The first interview will take place following the completion of the first block of elective posting, and the second interview will take place following the conclusion of the second block of elective posting. Results: We observed a statistically significant difference when two blocks were compared on the domains of efforts. Students have reported higher efforts toward clinical and surgical postings. We also observed that students reported a statistically significant level of frustration in block two. In our study, we found that research work was taken more during the second block as students were sensitized in the first block regarding research. Conclusion: In our study, we have observed that research activities are taken up and processed for presentation using biostatistics in the second block of elective if resource material and support are provided in the block one. Students develop a better understanding of research with proper training.